From Historic Inventory to Contemporary Display: The Collections of the Zachęta — National Gallery of Art in Warsaw - Świtek, Gabriela (Actual Problems of Theory and History of Art, 2020)
The history of the post-war collection of the Zachęta — National Gallery of Art in Warsawis one of meanders of Polish cultural policy. Today gallery’s function is primarily as a place of exhibition (Kunsthalle). The collection of Polish art that was amassed here prior to the II World War now constitutes a substantial element in the inventories of the National Museum in Warsaw. However, one of the statutory requirements of Zachęta nonetheless remains “the collection, inventory and storage of contemporary works of art”. Zachęta’s current collection numbers 3598 works (Annual Report 2017). The works document a number of important phenomena in Polish art from the late 1940s until today, including different types of geometric abstraction, the metaphorical-expressive movement (a Polish version of surrealist tendencies), the new figurative movement, the Polish Colourist aesthetics, and the most recent tendencies, such as the socalled “critical art” of the 1990–2000s. In 1949 the Central Office for Art Exhibitions was founded and located in the Zachęta building. The collection accumulated during the Central Office for Art Exhibitions period of existence (until 1992) is not one that had a well-defined profile. Works were bought from exhibitions,competitions and sometimes simply as a form of aid to artists. The funds for purchase came from the Ministry of Culture and Art: from the Fund for the Development of the Visual Arts, or through the national ordering system of the Art Department in the Ministry. However, during the 1970s, works began to be acquired for the purposes of exhibitions and education. The most recent acquisitions are primarily of works by Polish contemporary artists exhibited at the gallery and of works co-produced by the Zachęta, whether inhouse or elsewhere (e.g. for the Polish Pavilion at the Venice Biennale). During the 1990–2000s the Zachęta has succeeded in putting together a collection of works by middle generation and young generation of Polish artists (such as, internationally renowned Paweł Athamer, Mirosław Bałka, Katarzyna Kozyra, Zbigniew Libera and Artur Żmijewski). Collection building is a significant part of the gallery’s contemporary policy. This is made possible by funds offered by sponsors (such as the ING Polish Art Foundation), funds obtained through the Ministry of Culture and National Heritage programme Collections — Regional Collections of Contemporary Art, and also funds generated by Zachęta specially for the purpose or donations of works by artists (crowdfunding). Works from the collection are also included in the Zachęta’s exhibition and educational programme. The focus of the paper is on the transition from the Zachęta’s historical inventories to the issues of collection’s contemporary forms of display.
Keywords: Zachęta; Polish art history; contemporary art